2008
DOI: 10.1300/j190v04n03_04
|View full text |Cite
|
Sign up to set email alerts
|

Countertransference Bias in the Child Custody Evaluator

Abstract: Concerns about bias which may arise in the child custody evaluation process have recently attracted critical attention. The types of biases addressed are those that primarily stem from cognitive psychology, as well as social and cultural sources of bias. Rarely discussed, however, is bias which can stem from evaluator countertransference, which if unrecognized can potentially lead to biased and non-objective recommendations. While one must strive to be objective and impartial, child custody evaluators are freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…A fourth type of bias in child custody evaluations is counter-transference reactions by evaluators (Pickar, 2007a(Pickar, , 2007b. Due to highly charged emotional issues in such evaluations, the evaluators' own personal issues or past experiences might impact their feelings and thoughts toward a parent and influence the findings and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…A fourth type of bias in child custody evaluations is counter-transference reactions by evaluators (Pickar, 2007a(Pickar, , 2007b. Due to highly charged emotional issues in such evaluations, the evaluators' own personal issues or past experiences might impact their feelings and thoughts toward a parent and influence the findings and recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…Hamel, Dufour, and Fortin (1993) note that a fundamental criticism of case studies is the lack of rigour in the collection of empirical materials, especially the risk of confirmation bias. To counter this bias, the case study benefits from the prior development of theoretical propositions to guide data collection and analysis, and structure the many variables of interest (Martindale & Gould, 2007; Pickar, 2008; Yin, 2003). For example, the theoretical model depicted in Fig.…”
Section: Case Study Methodology: Two Major Methodological Componentsmentioning
confidence: 99%
“…Importantly, there is no formal evaluation of the utility of CCEs in the court system to date (Kelly & Ramsey, 2009), although Maccoby and Mnookin (1992) have found that, of the nine percent of custody cases that were not settled by negotiation or mediation (n = 84), more than 50 percent (n = 49) settled after the custody evaluation. This suggests that the custody evaluation may have been partly instrumental in facilitating settlement where negotiation and mediation had not succeeded.f cre_1375 336..347 Over the past 20 years, experts have raised incisive criticisms of the science behind CCEs, including the limits of custody-relevant psychological knowledge (Tippins & Wittmann, 2005), the practice of focusing on adults rather than the child, the indiscriminate use of psychometric tests, evaluators in dual roles (Bow & Quinnell, 2004;Emery, Otto, & O'Donohue, 2005), the limits of mental health assessment practices (Trombetta, 1991), and the biases of evaluators (Pickar, 2008). While these are valid criticisms of the empirical science of CCE, the demands of custody disputes make CCEs necessary.…”
mentioning
confidence: 99%
“…Third, it is accepted by forensic evaluators that there will be a high percentage of difficult personalities or even parties with personality disorders within this population. For these reasons, the evaluator needs to guard for negative reactions or even counter-transference (Pickar, 2007). Evaluators, not infrequently, will find these folks to be not very likeable.…”
Section: Confirmatory Bias and The Ethical Expertmentioning
confidence: 99%